OPTIMIZATION OF HEALTH SERVICES FOR PRISONERS BY THE PEMATANGSIANTAR CLASS IIA CORRECTIONAL INSTITUTION - Sitorus, Johan; Yuska, Syahrial (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study aims to evaluate the quality of healthcare services provided in Pematangsiantar Class IIA Penitentiary and to identify potential optimization efforts. Employing a qualitative approach, this research involved observations, interviews, and document analysis. The findings indicate that, overall, the healthcare services in the penitentiary have met minimum standards. The dimensions of reliability and responsiveness were assessed as fairly good, reflected in the availability of healthcare personnel and the speed of response to inmate needs. However, several aspects require improvement, particularly related to the dimensions of tangibles (facilities and equipment), assurance (quality assurance), and empathy (care). Limitations in facilities and infrastructure, as well as the need to enhance staff capacity in providing more personalized services, are the main challenges. This study suggests the need for increased investment in healthcare facilities, ongoing training for staff, and active involvement of inmates in the evaluation and improvement of services. Keywords: Quality; Service; Health; Prison; Inmate